2023
DOI: 10.1038/s41380-023-02067-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neuroimaging epigenetic research: calling for an increased focus on development

Abstract: Epigenetic mechanisms, such as DNA methylation (DNAm), have gained increasing attention as potential biomarkers and mechanisms underlying risk for neurodevelopmental, psychiatric and other brain-based disorders. Yet, surprisingly little is known about the extent to which DNAm is linked to individual differences in the brain itself, and how these associations may unfold across development – a time of life when many of these disorders emerge. Here, we systematically review evidence from the nascent field of Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…For instance, studies have shown altered DNA methylation patterns in genes associated with amyloid-beta processing and tau phosphorylation in Alzheimer’s disease (AD) [ 122 ]. Similarly, in Parkinson’s disease (PD) [ 123 ], dysregulated DNA methylation has been observed in genes linked to mitochondrial function, dopamine signaling, and neuroinflammation [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, studies have shown altered DNA methylation patterns in genes associated with amyloid-beta processing and tau phosphorylation in Alzheimer’s disease (AD) [ 122 ]. Similarly, in Parkinson’s disease (PD) [ 123 ], dysregulated DNA methylation has been observed in genes linked to mitochondrial function, dopamine signaling, and neuroinflammation [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…The existing few studies in the field of neuroimaging epigenetics have widely focused on adult and clinical populations. A 2023 review published in Biological Psychiatry reported that only 21% of neuroimaging epigenetic studies explored developmental cohorts, and only 5% in childhood 11 . Even fewer neuroimaging epigenetic studies in developmental cohorts consider typical development; most examine environmental associations or clinical samples 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A 2023 review published in Biological Psychiatry reported that only 21% of neuroimaging epigenetic studies explored developmental cohorts, and only 5% in childhood 11 . Even fewer neuroimaging epigenetic studies in developmental cohorts consider typical development; most examine environmental associations or clinical samples 11 . Additionally, only ten longitudinal cohorts that track both DNAm and MRI in pediatric populations were noted in a systematic review 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to date have associated DNAm with schizophrenia using postmortem brain tissues, which cannot inform on developmental processes in living individuals (Lancaster, Morris, & Connelly, 2018). Neuroimaging epigenetics can help to bridge this gap by combining DNAm from peripheral tissues with in vivo brain imaging techniques, such as structural magnetic resonance imaging (MRI; Walton et al., 2023; Wheater et al., 2020). This approach could provide novel insights into epigenetic processes contributing to brain features associated with schizophrenia risk, such as LVV enlargement.…”
Section: Introductionmentioning
confidence: 99%